Impact of Business Environment on Trade Flows: Evidence from RCEP Countries - Sy, Vo; Karlsson, Thomas; Mingxia, Zhu (Global business review, 2025)
This study is a pioneering investigation of the business environment’s impact on trade flows among Regional Comprehensive Economic Partnership signatories. It measures the impact on trade flows using a gravity model, including factors such as business regulations, infrastructure and border and transport efficiency. A two-step Heckman procedure estimates the probability of receiving inward foreign direct investment. The results indicate that business regulations have a positive impact on trade flows and the probability of receiving investment. In addition, border and transportation efficiency is correlated with increased bilateral trade. However, infrastructure investment, although crucial for promoting bilateral trade, proves negatively correlated with receiving investment. These results are robust to standard econometric checks. Thus, this study indicates that partnership signatories must focus on improving their domestic business environments to reap the full benefits of the trade agreement.